55 NOVEL ANALOGS OF FTY720 PROMOTE PULMONARY VASCULAR BARRIER FUNCTION. (1st March 2006) - Camp, S. M.; Dudek, S. M.; Chiang, E. T.; Singleton, P. A.; Bittman, R.; Sanchez, T.; Hla, T.; Garcia, J. G.N.
Abstract : Rationale: Modulation of pulmonary vascular barrier function is an important clinical goal given the devastating effects of vascular leak in ARDS. We and others have demonstrated that FTY720, an analog of the potent barrier-enhancing phospholipid sphingosine 1-phosphate (S1P), is also barrier protective through incompletely characterized mechanisms. We utilized various FTY analogs to better define FTY effects on endothelial cell (EC) barrier function. Methods/Results: FTY (1 μM) significantly increased cultured human pulmonary artery EC barrier function in a sustained manner as measured by transendothelial electrical resistance (TER) but with a delayed onset and slower rate of TER rise relative to S1P (1 μM). Previous siRNA experiments have suggested that FTY does not exert its barrier-enhancing effects through the same S1P1 R receptor required for S1P. We now report that FTY also increases TER in EC derived from embryonic S1P1 R -/- mice, providing further support for a novel FTY barrier-enhancing pathway. In addition, S1P3 R is not the responsible receptor as S1P3 R siRNA did not alter FTY-induced TER increases. Increasing concentrations of phosphorylated FTY (0.1-50 μM) produced a faster TER elevation rate of onset than FTY itself but never reached the rate of rise observed with S1P. (R)-phosphonate and enephosphonate analogs of FTY (1-50 μM) produced rapid TER elevations similar to S1P, while the (S)-analogs were less potent or even barrier-disruptive. Both (R)- and (S)-regioisomers of FTY were barrier disruptive. Conclusion: These results support a novel mechanism of FTY action and provide further insights into the vascular barrier enhancing effects of FTY720. HL58064, HL70013-01, FTY720 supplied by Novartis.